IMPLEMENTASI KEGIATAN SRADHA DAN BHAKTI DALAM MENANAMKAN KARAKTER RELIGIUS SISWA - Hukunala, Hendro; I Wayan Rudiarta; Ni Wayan Ria Lestari (Jawa Dwipa, 2024)
Sradha and bhakti activities are important things that students must carry out at school. At Elementary School 11 Cakranegara, sradha and bahkti activities take place with students playing around and even mocking, slandering, each other. The purpose of the research, is to conduct a study related to the implementation of sradha and bhakti activities in instilling the religious character of students, at Elementary School 11 Cakranegara. This research uses a qualitative method with a descriptive narrative approach. The data collection techniques used were non-participant observation, interviews, and documentation. Data analysis techniques used were data reduction, data display, data verification, and conclusion drawing. The theories used are Social Learning Theory and Moral Development Theory. The results of this study indicate that the Implementation of Sradha and Bhakti Activities in instilling the religious character of students, namely the 7S Tradition, worship before and after learning, carrying out tri sandya, celebrating religious holidays, practicing tolerance towards people of other religions, having facilities for religious activities. The problems faced by teachers in instilling religious character are lack of student awareness, lack of parental motivation, lack of prayer places. Preventive steps taken by teachers to overcome problems in the application of sradha and bhakti, practice of sradha and bhakti, development of social skills, supervision and evaluation, intrensive communication between teachers and parents, development of spiritual skills.